2012 19th IEEE International Conference on Image Processing 2012
DOI: 10.1109/icip.2012.6467220
|View full text |Cite
|
Sign up to set email alerts
|

Student's t robust bundle adjustment algorithm

Abstract: Bundle adjustment (BA) is the problem of refining a visual reconstruction to produce better structure and viewing parameter estimates. This problem is often formulated as a nonlinear least squares problem, where data arises from interest point matching. Mismatched interest points cause serious problems in this approach, as a single mismatch will affect the entire reconstruction. In this paper, we propose a novel robust Student's t BA algorithm (RST-BA). We model reprojection errors using the heavy tailed Stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…On the other hand, BA which is usually solved using the LevenbergMarquardt numerical method [51] is highly sensitive to the presence of feature correspondence outliers [4]. Mismatches can cause problems for the standard least squares approach; as stressed in [9] even a single mismatch can globally affect the result. This leads to sub-optimal parameter estimation, and in the worst case a feasible solution is not found [4,35].…”
Section: Adaptive Robust Error Functionmentioning
confidence: 99%
“…On the other hand, BA which is usually solved using the LevenbergMarquardt numerical method [51] is highly sensitive to the presence of feature correspondence outliers [4]. Mismatches can cause problems for the standard least squares approach; as stressed in [9] even a single mismatch can globally affect the result. This leads to sub-optimal parameter estimation, and in the worst case a feasible solution is not found [4,35].…”
Section: Adaptive Robust Error Functionmentioning
confidence: 99%
“…Mismatches in the feature track observations can strongly undermine the bundle adjustment performance, leading to failure or strong biases [3,29]. We remove erroneous matches by means of a distance ratio test with a relative threshold of 0.6 [28].…”
Section: Pairwise Matchingmentioning
confidence: 99%
“…The rejection of points whose reprojection error exceeds a certain threshold after a series of initial iterations is a popular strategy [39,44,29]. Other approaches use cost functions that enforce robustness to occasional large residuals, or employ iterative reweighting according to the reprojection error of each observation [43,3,47].…”
Section: Cost Functions and Reprojection Error Based Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…This density was also successfully used in the Kalman smoothing context [8], where it was suggested that the EM algorithm can be used to fit meta-parameters. Recent work using the Student's t distribution [2,3,1] has side-stepped the problem, using fixed values for σ and k.…”
Section: Degrees Of Freedom and Variance Estimation For Student's T Fmentioning
confidence: 99%